Tactile Learning in Drama: Impacts on Students’ Vocabulary Acquisition and English Learning Engagement - Sihombing, Amrina; Zasrianita, Fera; Andriadi, Andriadi; Andri, Saputra (PANYONARA: Journal of English Education, 2025)
Various efforts have been made to enhance vocabulary acquisition and students’ engagement in English classrooms; however, studies that specifically highlight the application of tactile learning integrated with drama activities remain relatively limited. This study seeks to fill that gap. It aims to examine the impacts of tactile learning in drama activities on the English vocabulary acquisition and classroom engagement of eighth-grade students at SMPIT Khairunnas Bengkulu City during the English learning process. It used a case study with quantitative and qualitative approaches. The data were collected by conducting pre-test and post-test, Focus Group Discussion (FGD), Observation, and documentation. There were 87 students as respondents of the research. The result showed that the implementation of tactile learning through drama could improve students’ English vocabulary acquisition. The use of tactile learning approach in drama activities gave positive impacts in improving students’ engagement in English class. The result of the research strengthens opinion that tactile learning in drama activities is an effective and fun learning method to improve students’ English vocabulary acquisition and engagement in English class.